FEATURES OF REHABILITATION OF PATIENTS AFTER GASTRIC RESECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The operation consists in mobilizing the stomach with the intersection of ligaments and all blood vessels supplying the stomach. Then the stomach is cut off from the esophagus and from the duodenum. The stump of the duodenum is being treated. Rehabilitation of patients after gastric resection is a multifaceted process that requires an integrated approach and attention to the individual characteristics of the patient. The main tasks of rehabilitation are the restoration of proper nutrition, correction of digestive disorders, prevention of complications, as well as psychoemotional support.The first stage of rehabilitation includes medical monitoring aimed at monitoring the patient's condition, digestive functions and general well-being. It is important to introduce a diet rich in proteins and vitamins, which promotes tissue healing and strengthens the immune system. The gradual expansion of the dietary intake helps to avoid complications and provide the necessary amount of calories.